RELATIONER I RÖRELSE: En fallstudie av mellananvändningen på Botulfsplatsen - Engel,Emilia (2025)
This thesis examines the temporary use and development of Botulfsplatsen, a future central public square in Lund, Sweden. Previously a node for city buses, the municipality decided to repurpose the site for interim use as a way to test and activate the square prior to its permanent reconstruction. Drawing on theories of placemaking, temporary use, and relational geography, the study addresses two main questions: (1) Which actors and interests were represented during the interim use of Botulfsplatsen, and how do these relate to Lund Municipality’s overarching strategies and goals? and (2) In what ways have interactions between these actors and interests influenced the ongoing transformation process of Botulfsplatsen?. The empirical material is based on four semi-structured interviews with two key stakeholders from municipal departments, the city’s tourism and events agency, and the owner of a restaurant located at the square. In addition, a document analysis was conducted of five municipal documents and strategies, as well as newspapers, meeting minutes, and three municipal websites. The findings show that the interim use of Botulfsplatsen was shaped by a complex network of actors and interests, including municipal departments, Visit Lund, restaurant businesses, and organisations promoting local commerce. These actors pursued overlapping yet distinct goals, such as activating the square through cultural events, supporting local businesses, and enhancing green values in the city centre. Their interactions, characterized by both collaboration and negotiation, have directly informed the ongoing transformation process square, which will feature outdoor dining areas, greenery, a public artwork, and a flexible space for future temporary uses.
Keywords: Botulfsplatsen; interim use; temporary use; placemaking; relational geography